Validitas Website sebagai Media Pembelajaran untuk Meningkatkan Keterampilan Berpikir Kreatif pada Materi Ikatan Kimia - Selvia Nuraini; Rusly Hidayah (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2023)
The lowness of creative thinking skills of students on chemical bonding can be improved by making good quality learning media that using websites. Therefore, this research was carried out to determine the validity of the website as a learning media in order to improve creative thinking skills on chemical bonding. This study uses the 4D model (define, design, develop, & disseminate), but it is limited to the development stage. The content and construct validity of the website was obtained using a validation sheet. The percentage of content validity obtained from the suitability of website with learning objectives, material, and indicators of creative thinking skills is 91.22%. While the percentage of construct validity obtained from the ease of navigation, presentation, and language on the website is 88.57%. So, the developed website is considered as very valid to improve students' creative thinking skills